An efficient RuCl3·H2O/I2 catalytic system: A facile access to 3-aroylimidazo[1,2-a]pyridines from 2-aminopyridines and chalcones - P.V. Sri Ramya; Srinivas Angapelly; Chander Singh Digwal; Upasana Yadav; Bathini Nagendra Babu; Ahmed Kamal (Journal of Saudi Chemical Society)
A simple and efficient protocol has been demonstrated for the preparation of densely functionalized 3-aroylimidazo[1,2-a]pyridines from 2-aminopyridines and chalcones using RuCl3·H2O/I2 catalytic system. The advantages, such as low catalyst loading, broad substrate scope with respect to substitutions on aminopyridines as well as chalcones, stability of heterocycles such as thiophene under the reaction conditions, operationally simple procedure and higher yields makes this approach remarkable for synthetic applications.